Between all-for-one and each-for-himself: On-farm competition for labour as determinant of wetland cropping in two Beninese villages - Paresys, L.; Malézieux, E.; Huat, J.; Kropff, K.J.; Rossing, W.A.H. (Elsevier, 2018)
In sub-Saharan Africa, unexploited land and water resources in wetlands represent an important potential for intensified, sustainable and food-secure farms through rice production and market gardening. The lack of uptake of cropping in wetlands may be related to the ways in which resources are divided between family fields and individual fields. The management system on sub-Saharan African farms comprises a family management unit or a combination of a family management unit and one or more individual management units. The family management unit or the farm head controls production in family fields to satisfy family needs while the individual management units control production in individual fields to satisfy individual needs. Our objective was to investigate the diversity in farm management systems and the resulting uptake of cropping in wetlands for different farm types, as the first step towards suggestions for enhancing rice production and market gardening in wetlands. We studied farms in two case-study villages in Benin: Zonmon in the southern part and Pelebina in the north-western part. Farm typologies were developed based on random samples of 51 out of 134 farms (38%) from Zonmon and 50 out of 146 farms (34%) from Pelebina by combining principal component analysis and Ward's minimum variance clustering. Variables included in the PCA were related to levels of resource endowment (e.g., amounts of land, family labour, cash for purchasing chemical inputs and hiring labour) and to resource-use strategies including resource division between family fields and individual fields, and between uplands and wetlands. We identified 3 farm types in Zonmon and 5 farm types in Pelebina based on differences in resource-use strategies and in resource endowment. We found no trade-off between the existence of individual fields and the area under rice and market garden crops in wetlands. Labour abundance was the main factor driving both the occurrence of individual fields and the expansion of cropping in wetlands. Differences in labour division strategies between family and individual fields among farm types reflected differences in food and cash division strategies. Land use appeared strongly motivated by food self-sufficiency objectives and labour productivity, leading to prioritisation of upland over wetland areas. In wetlands, most farm types opted for cultivating market garden crops during the dry season when labour demand for upland fields was low. Our results indicate that increasing labour productivity in food crops and in rice and market garden crops would enhance the uptake of rice and market garden crops in wetlands. Creating credit facilities would increase the labour resource and allow farmers to hire labour, further contributing to wetland use. We discuss the relevance of a systemic farm analysis that enables distinguishing family and individual fields for understanding farm uptake of rice and market garden crops in wetlands.